Analysis of sailing boat track in virtual simulator with different level skill sailor - Manzanares Serrano, A.; Segado Segado, F.; Menayo Antúnez, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Physical attitude, speed of the boat and tactical intelligence are the main elements of the competitive movement in dinghy sailing (Spurway, Legg & Hale, 2007). The aim of this research has been analyze and compare the boat track by sailors of different levels and related them with the success they got at the start. Methods: The participants of this study have been six Optimist class sailors from Murcia (Spain), between the ages of 12 to 15. The level of the sailors is determined by the position they have in the ranking. Two of them are on the top of the classification, another two are on the middle positions and the last two are on the lower positions of the ranking. The registry of the boat track by the sailors was carried out with the sailing simulator VSail-Trainer®. Research variables were the boat track and the speed of the boat on second 0,0. The boat race consisted of a simulated start, with stable conditions of wind, opponent and sea. The simulated start presented the same conditions that can be found in a real start. Result: The results show that expert sailors do a better performance of boat track, due to the fact that they reach the second 0.0 in a closer position to the start line and at a better speed than sailors with less experience. It must be highlighted that the rest of the sailors of the middle positions of the ranking perform a boat track different than the rest, even surpassing the start line before the 0.0. Beginners perform the less stable boat track and are the last ones to surpass the start line. Discussion: Expert sailors show the best behaviour, which consists on reaching the 0.0 second as close as possible to the start without surpassing it. This can be due to a major capacity to assimilate environmental changes and adapt to them that expert sailors have in relation to beginners (Rocha, Araujo & Serpa, 1995). The differences shown by those sailors in the middle positions of the ranking in relation to those of the lower positions can be due to the capacity to look for a better strategy, which is developed as one gains experience (Walls, Bertrand, Gale y Saunders, 1998).